Bringing Paved Roads to the Hinterland : A Cost-Saving Way to Speed Travel and Transport - Whalley, Oliver George (World Bank, Washington, DC, 2016)
Extreme poverty is a predominantly rural phenomenon, and the poor quality of roads linking remote areas to market centers is one of its distinguishing features. The time and cost of moving goods over poor roads makes rural traders uncompetitive. The problem often remains unsolved because sparse traffic makes it cost-prohibitive to pave rural roads by traditional means. Developing countries need affordable options for extending paved road networks into rural areas. A versatile new construction method using low-cost concrete poured into flexible plastic webbing offers a promising alternative. These geo cell pavements, cost less to build and maintain than concrete, asphalt, or chip seal pavements. The new pavement technology has been used in Africa, the Middle East, Australia, and the Pacific, offering an affordable way to improve accessibility for poorer remote areas. Geo cell pavements that link rural traders and farmers to market centers could become an important tool in the effort to eliminate extreme poverty.